Digital Exclusion of Seniors in Polish Rural Areas in the Context of Well-Being - Dudek-Frysiak, Honorata; Chomiak-Orsa, Iwona (Wykluczenie cyfrowe seniorów na obszarach wiejskich w Polsce – analiza teoretyczna i empiryczna, 2023)
Aim: The aim of the article is to show the level of digital exclusion of seniors in Polish rural areas in the context of assessing the level of well-being. Methodology: The article is based on both theoretical and empirical research concerning the issue of digital exclusion among older adults. Theoretical research allowed the authors to determine the level of academic interest in the topic, assess the extent of digital exclusion, and identify its main causes. Methods included content analysis of selected academic publications, governmental reports, and EU documents. The empirical part presents the results of quantitative research conducted in 2017 and 2022 in the Lower Silesian Voivodeship, aimed at assessing the degree of digital exclusion among Polish seniors living in rural areas. Results: The literature analysis revealed that the topic of digital exclusion among rural seniors is underrepresented in Polish academic discourse, despite growing global attention. The empirical findings confirmed a high level of digital exclusion among seniors in rural areas of Lower Silesia. Implications and recommendations: The results highlight the urgent need for action to reduce this gap. Digital technology use is fundamental to functioning in modern society, and lack of access significantly impacts the quality of life and well-being of older people. Given the projected demographic trends indicating a growing population aged 60 and over, increased scholarly and social focus on the needs of this group – particularly in the context of digital integration – is essential. Originality/value: The scientific considerations presented in the article are intended to contrast the point of view presented in the literature n relation to the real state of digital exclusion of seniors.
Business Informatics = Informatyka Ekonomiczna, 2023, Nr 1-2 (65-66), s. 11-22
Keywords: digital exclusion; rural areas; seniors; well-being; wykluczenie cyfrowe; seniorzy; obszary wiejskie; dobrostan